Estimation of Carbon Storage Potency of Acacia and Eucalyptus Mixed Stand in Mine Reclamation at PT. Bukit Asam (Persero) Tbk - Omo Rusdiana; Dadan Mulyana; Cikal Utami Willujeng (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2013)
Reclamation is an effort to recover ex-mined land to its original function. Revegetation that can be conducted during reclamation is by planting acacia and cajuput. One of the reclamation results is carbon being absorbed and saved in biomass form. Therefore the amount of saved carbon can be estimated from potential biomass. Factors that can affect amount of biomass are age of standing tree, history of vegetation development, climate, and composition and structure of stand. The research shows that biomass potency in Block B (16,70 ton/ha) is larger than that of Block A (14,24 ton/ha). Estimation results of saved carbon potency show that it is directly related with biomass potency. Carbon saved in Block A is 4,14 ton/ha and that of Block B is 5,56ton/ha. This research shows that the ability of mixed stand of acacia and cajuput in saving carbon has not been optimum yet.Keywords: acacia, cajuput, reclamataion, carbon storage.